113k views
3 votes
Pls help me In this asap

Pls help me In this asap-example-1

2 Answers

3 votes
3x^2+1/ (1-x) (x+3) you have to simplify the expression
Pls help me In this asap-example-1
User Himanshu Singh
by
6.3k points
2 votes

Answer:

1

Explanation:

Please see the attached picture for full solution.

☆5th line

Neumerator:

(a +b)²= a² +2ab +b²

Thus, (1 +x)²= 1² +2(1)(x) +x²

Denominator:

(a -b)²= a² -2ab +b²

Thus, (1 -x)²= 1² -2(1)(x) +x²

Pls help me In this asap-example-1
User Telebog
by
5.5k points